2010
DOI: 10.1042/bj20090835
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of pig CMP-N-acetylneuraminic acid hydroxylase for the synthesis of N-glycolylneuraminic acid as the xenoantigenic determinant in pig–human xenotransplantation

Abstract: In the present study, the pig CMP-N-acetylneuraminic acid hydroxylase gene (pcmah), a key enzyme for the synthesis of NeuGc (N-glycolylneuraminic acid), was cloned from pig small intestine and characterized. The ORF (open reading frame) of pcmah was 1734 bp, encoding 577 amino acids and consisting of 14 exons. Organ expression pattern analysis reveals that pcmah mRNA is mainly expressed in pig rectum, tongue, spleen and colon tissues, being the most highly expressed in small intestine. In the ectopic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 39 publications
1
46
0
Order By: Relevance
“…Although this tissue contains more total Sias than any other (34), Neu5Gc is reported to be present at only trace levels, if at all. Studies of mouse and pig tissues have accordingly found Cmah mRNA to be undetectable in brain (35,36). As we confirm and expand in this study, no other tissue displays this unusual suppression of Neu5Gc expression across vertebrate taxa.…”
supporting
confidence: 73%
“…Although this tissue contains more total Sias than any other (34), Neu5Gc is reported to be present at only trace levels, if at all. Studies of mouse and pig tissues have accordingly found Cmah mRNA to be undetectable in brain (35,36). As we confirm and expand in this study, no other tissue displays this unusual suppression of Neu5Gc expression across vertebrate taxa.…”
supporting
confidence: 73%
“…1b). This result entirely corresponded with the previously described tissue expression patterns of pcmah, indicating that 5'pcmah-2 is responsible for housekeeping expression [16]. The different lengths of pcmah promoter regions were PCR-amplified from the pig BAC clone containing the pcmah gene (Fig.…”
Section: Identification Of Housekeeping Promoter Region Of Pcmahmentioning
confidence: 63%
“…Our previous study [16] isolated two 5'alternative splicing variants of pcmah and demonstrated their tissue-specific expression pattern, as illustrated in Fig. 1a.…”
Section: Identification Of Housekeeping Promoter Region Of Pcmahmentioning
confidence: 95%
See 1 more Smart Citation
“…It is important that the nature of immune suppression in gangliosides is determined because of their potential for reducing xenotransplantation immune rejection. Moreover, the mechanism of cell-mediated xenotransplantation rejection is only partially understood (Mejia-Laguna et al 1971;Ozawa et al 1992;Lin et al 1997;Magnusson et al 2005;Jung et al 2009;Song et al 2010;Liu & Yang 2012). In particular, it is likely that the innate immunity effects that are mediated by gangliosides will influence cell functions and contribute to the strength and complexity of xenotransplantation rejection (Platt et al 1991).…”
Section: Discussionmentioning
confidence: 99%